Pupil constrictions to subjective brightness as a gateway to probe consciousness in non communicating patients - Aude Sangare; Cécile Eymond; Lise Jodaitis; Sophie Demeret; Benjamin Rohaut; Lionel Naccache (Scientific Reports)
Abstract Retinal illumination primarily determines pupil size, yet extra-retinal factors like subjective brightness also influence pupillary responses. Previous works reported that in healthy individuals, stimuli whose semantic content evokes brightness cause greater pupillary constriction than control stimuli of similar luminance. This study adapted this approach and tested a passive task to assess consciousness levels of non-communicating patients in intensive care unit. In ten healthy participants and seventeen patients with Disorders of Consciousness (10 in a Minimally Conscious State, 6 in Vegetative State also coined Unresponsive Wakefulness Syndrome), 1 in Emergence from Minimally Conscious State), we measured pupillary responses to photographs of the sun and control stimuli of matched luminance (moon photographs, scrambled sun images, uniform gray squares). At the group level, both healthy participants and Minimally Conscious State patients showed greater pupil constriction for the sun photographs compared to control pictures which elicited a pupillary dilatation. In Vegetative State/ Unresponsive Wakefulness Syndrome patients, this subjective brightness effect on pupillary diameter was not significant. Notably, this effect was observed in only one Vegetative State patient, who regained consciousness a few weeks after the evaluation. The results support that pupillary response to subjective brightness could be a novel method to assess residual cognition at the bedside in non-communicating patients.